Northeast Kansas City: a study of neighborhood diversity and urban design - Wencel, Eric (Kansas State University, 2013)
This report acts as an independent study which contributes to the author’s participation in the 2012-2013 Kansas City Design Center planning and urban design studio. The project focuses on Independence Avenue in Kansas City, MO, the commercial and transportation backbone of seven neighborhoods, collectively known as Northeast Kansas City. Residents of these neighborhoods place great value in the “diversity” which exists in their neighborhoods, and have made it clear that this should be encouraged as a major part of the Northeast’s identity. This inspired the author to pursue a deeper understanding of the idea of diverse neighborhoods, how they fit into the “sustainable development” consciousness, and ultimately how one can plan and design for neighborhood diversity. The resulting study consisted of two levels of analysis. First, analyzing the mixture of age, sex, household type, race, and income level at the regional, city, and neighborhood scale, in order to understand what social diversity means in the Kansas City context, and define how diverse Northeast Kansas City neighborhoods are. The second was an analysis of conditions in the built environment. Using the Scarritt Renaissance and Lykins neighborhoods, and a common commercial district/social seam between the two as a case study, the author intended to analyze how successful or unsuccessful the typical Northeast neighborhood is at encouraging diverse populations. Ultimately, these analyses yielded two main conclusions. The first is that neighborhood diversity means drastically different things depending on how you define and measure the term. The second is the notion that social seam commercial districts are a unique spatial typology, which requires special design consideration, and can be most catalytic to setting the tone for future growth. Finally, the author concludes with the idea that one cannot necessarily plan or design for diverse neighborhoods, but they can do so in ways which empower diversity, and be conducive to things which support diverse neighborhoods. However, the built environment only makes up a portion of the things which influence neighborhood diversity, requiring an involved and invested community who values social diversity in their neighborhood.
Keywords: Urban planning; Urban design; Diversity; Kansas City; Social seams; Neighborhood; Urban Planning (0999)